Penerapan Problem Based Learning dalam Pembelajaran IPA dan Bahasa Indonesia Tema Perubahan Lingkungan SDN Patrang 02 - Kamila, Nayla Rizqi; Prayogo, Muhammad Suwigyno; Aisyafah, Heny; Wulandari, Dewi Indah (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to describe the application of the Problem-Based Learning (PBL) model in integrating Science and Indonesian Language learning on the theme of “Environmental Change” at SDN Patrang 02. This study uses a descriptive qualitative approach with teachers and fifth-grade students as the research subjects. Data collection techniques include observation, interviews, and documentation. Data analysis was conducted using thematic analysis, with stages of coding, theme identification, interpretation of meaning, and drawing conclusions based on patterns of findings that emerged from field data. The results showed that the application of the Problem Based Learning model was able to increase student learning activity, develop critical thinking skills, and improve language skills through discussion and report writing activities. Students showed high enthusiasm in solving real problems related to environmental changes around them. In conclusion, the application of the Problem-Based Learning model is effective in integrating science and Indonesian language learning and is able to improve students' critical thinking and literacy skills at SDN Patrang 02.